Air pollution and the skin - Drakaki, Eleni; Dessinioti, Clio; Antoniou, Christina V. (Frontiers in Environmental Science, 2014)
The increase of air pollution over the years has major effects on the human skin. The skin is exposed to ultraviolet radiation (UVR) and environmental air pollutants such as polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), oxides, particulate matter (PM), ozone (O3), and cigarette smoke. Although human skin acts as a biological shield against pro-oxidative chemical and physical air pollutants, the prolonged or repetitive exposure to high levels of these pollutants may have profound negative effects on the skin. Exposure of the skin to air pollutants has been associated with skin aging and inflammatory or allergic skin conditions such as atopic dermatitis, eczema, psoriasis or acne, while skin cancer is among the most serious effects. On the other hand, some air pollutants (i.e., O3, nitrogen dioxide, and sulfur dioxide) and scattering particulates (clouds and soot) in the troposphere reduce the effects of shorter wavelength UVR and significant reductions in UV irradiance have been observed in polluted urban areas.